Cdx1 induced intestinal metaplasia in the transgenic mouse stomach: comparative study with Cdx2 transgenic mice. Issue 10 (10th September 2004) - Mutoh, H; Sakurai, S; Satoh, K; Osawa, H; Hakamata, Y; Takeuchi, T; Sugano, K
Abstract : Background and aims: Gastric intestinal metaplasia, which is mainly induced by Helicobacter pylori infection, is thought to be a precancerous lesion of gastric adenocarcinoma. Intestinal metaplastic mucosa expresses intestine specific homeobox genes, Cdx1 and Cdx2, in the human gastric mucosa. We and others have reported that ectopic expression of Cdx2 in the gastric epithelium generates intestinal metaplasia in the transgenic mouse model. Methods: To clarify the differences in the roles of Cdx1 and Cdx2 in intestinal metaplasia, we generated transgenic mice expressing Cdx1 in the gastric mucosa and compared Cdx1 induced gastric mucosal morphological changes with Cdx2 induced intestinal metaplasia. Results: The gastric mucosa in Cdx1 transgenic mice was completely replaced by intestinal metaplastic mucosa, consisting of all four intestinal epithelial cell types: absorptive enterocytes, goblet, enteroendocrine, and Paneth cells. Paneth cells, which were not recognised in Cdx2 transgenic mice, were in the upper portion of the intestinal metaplastic mucosa. Pseudopyloric gland metaplasia, which was induced in Cdx2 transgenic mice, was not recognised in Cdx1 transgenic mice. Proliferating cell nuclear antigen (PCNA) positive cells were diffusely scattered in Cdx1 induced intestinal metaplastic mucosa while PCNA positive cells in Cdx2 induced intestinal metaplastic mucosa were in the base of the metaplastic mucosa. Intestinal metaplastic mucosa of Cdx1 transgenic mouse stomach was significantly thicker than that of wild-type or Cdx2 transgenic mouse stomach. Conclusions: We have confirmed that Cdx1 induced gastric intestinal metaplasia but that it differed from Cdx2 induced intestinal metaplasia in differentiation, structure, and proliferation.